2011
DOI: 10.1007/978-3-642-22006-7_56
|View full text |Cite
|
Sign up to set email alerts
|

Popular Matchings in the Stable Marriage Problem

Abstract: Abstract. The input is a bipartite graph G = (A ∪ B,E) where each vertex u ∈ A ∪ B ranks its neighbors in a strict order of preference. This is the same as an instance of the stable marriage problem with incomplete lists. A matching M * is said to be popular if there is no matching M such that more vertices are better off in M than in M * . Any stable matching of G is popular, however such a matching is a minimum cardinality popular matching. We consider the problem of computing a maximum cardinality popular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
91
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(92 citation statements)
references
References 14 publications
0
91
0
1
Order By: Relevance
“…Thus, the device can balance between the achievable rate and the correlation factor between device i and the devices assigned to SBS s. In fact, the second term in (11) enables a device i to report its information to an SBS that cannot get the same information from its assigned devices. Using the utility in (11), the preference relations of the devices can be given by:…”
Section: Utility and Preference Relations Of The Devices And Sbssmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the device can balance between the achievable rate and the correlation factor between device i and the devices assigned to SBS s. In fact, the second term in (11) enables a device i to report its information to an SBS that cannot get the same information from its assigned devices. Using the utility in (11), the preference relations of the devices can be given by:…”
Section: Utility and Preference Relations Of The Devices And Sbssmentioning
confidence: 99%
“…To define the most popular matching [11,12], we introduce the notion of a vote that allows every SBS and device to vote for its preferred matching. For a device i, the vote function…”
Section: Proposed Correlation-aware Cell Association Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…He also showed that if all preference lists are strict, then any stable matching is popular; thus a popular matching always exists and can be found in linear time using the well-known deferred acceptance algorithm of Gale and Shapley (1962). Huang and Kavitha (2013) later gave a characterization of popular matchings based on augmenting paths. They also came up with an O(m) algorithm to test whether a given matching is popular.…”
Section: Two-sided Modelmentioning
confidence: 99%
“…As demonstrated by this instance, a strikingly important feature of popular matchings is that they beat stable matchings in size. As a matter of fact, any stable matching is a minimum size popular matching (Huang and Kavitha, 2013). The size of a stable matching in G can be as small as |M max |/2, where M max is a maximum matching in G. Relaxing stability to popularity yields larger matchings and it is easy to show that a largest popular matching has size at least 2 3 • |M max |.…”
Section: Finding a Max Size Popular Matchingmentioning
confidence: 99%